P478 Treatment with ferric maltol associated with improvements in quality of life for IBD patients with iron deficiency anaemia. (16th January 2018) - Schmidt, C; Baumgart, D; Bokemeyer, B; Büning, C; Howaldt, S; Stallmach, A; Singfield, C; Tremblay, G; Jones, T
Abstract: Background: The Phase III, AEGIS study ( N = 128) demonstrated the efficacy and safety of ferric maltol for the treatment of iron deficiency anaemia (IDA) in patients with inflammatory bowel disease (IBD). 1, 2 Patient health-related quality of life (HRQOL) was measured using the SF-36 questionnaire during the double-blind and the 52-week extension phase. Meanwhile, the EQ-5D instrument is the measure of HRQoL preferred by health technology assessment (HTA) agencies, such as NICE. An established, validated algorithm 3 exists which can convert the SF-36 to the EQ-5D. Methods: We converted the SF-36 outcomes to EQ-5D scores. We compared the mean EQ-5D at Week 12 in the ferric maltol group (FM) to the placebo group (PBO). Next, we pooled the two Week 0 outcomes for FM and PBO and compared that to Week 36 in FM. Finally, the pooled Week 0 for FM and PBO result was compared with Week 36 from FM pooled with Week 48 in PBO, reflecting the delayed start to treatment in that group. Results: At Week 0, FM recorded a mean of 0.812 (SE: 0.02) and PBO was 0.797 (SE: 0.02). The mean difference is 0.01 (SE: 0.03, p = 0.622). At Week 12, FM was 0.844 (SE: 0.021) and for PBO it was 0.804 (SE: 0.023), showing a mean difference of 0.0396 (SE: 0.031, p = 0.204). At Week 36, patients in FM alone reported a mean of 0.888 (SE: 0.023) while FM and PBO patients pooled at Week 0 have a mean of 0.804 (SE: 0.015). Comparing these two means yields a difference of 0.083 (SE: 0.034, p = 0.016). Pooling Week 36 for FM with Week 48 for PBO records a score of 0.861 (SE: 0.021) and comparing to the pooled Week 0 mean yields a difference is 0.057 (SE: 0.03, p = 0.045). Conclusions: This post-hoc evaluation of outcomes from the AEGIS phase III study indicates that ferric maltol has a significantly beneficial effect on HRQoL of patients with IBD and IDA. Mean HRQOL was restored to population norms expected for the patient age profile. 4 The calculated change in HRQoL score was consistent with previous studies that examined the HRQoL burden of IDA, adding to the validity of the demonstrated effect. 5 References: 1. Gasche. Ferric maltol is effective in correcting iron deficiency anaemia in patients with inflammatory bowel disease: results from a phase-3 clinical trial programme. Inflamm Bowel Dis, 2015;21:579–588. 2. Schmidt. Ferric maltol therapy for iron deficiency anaemia in patients with inflammatory bowel disease: long-term extension data from a phase 3 study, Aliment Pharmacol Ther, 2016;44:259–270. 3. Ara and Brazier. Deriving an algorithm to convert the eight mean SF-36 dimension scores into a mean EQ-5D preference-based score from published studies (where patient level data are not available), J. Value Health, 2008;11:1131–1143. 4. Szende. Self-reported population health: an international perspective based on EQ-5D. Springer, Dordrecht, vol 3, 2014. 5. Covic. Real-world impact of cardiovascular disease and anemia on quality of life and productivity in patients with non-dialysis-dependent chronic kidney disease. Adv Ther, 2017;34:1662–1672.